Political economy - Comyn, Sarah (Abingdon, Oxon ; New York, NY : Routledge, 2025)
Providing a short take' on the long history of political economy, this book examines both the storiesaboutand thosewithineconomics. It traces the history of political economy from its beginnings in the Scottish Enlightenment; through its disciplinary demarcation as a science in the nineteenth century that saw its differentiation from literary, aesthetic, and moral discourses; andtoits emergence as the amoral' market-driven neoliberalism that dominates economic theories and policies today. In exploring the long history of economic thought, it examines and challenges both Enlightenment and contemporary grand narratives such as the stadial theory of progress, the Great Divergence' and the Great Convergence' that have divided the world into global norths and souths according to their economic advantages. It concludes with a study of currency as both a medium of monetary exchange and a term that denotes prevalence and acceptance to explore political economy's continuous engagement with the problem of representing value through money. Part of the series Short Takes on Long Views, this bookwill appeal to a traditional academic audience of scholars and students, and to a wider public audience of informed non-fiction readers interested in the long history of economics.
Keywords: Economics -- History; HISTORY / Modern / 18th Century; POLITICAL SCIENCE / General